BDNF Val66Met and 5-HTTLPR Genotype are Each Associated with Visual Scanning Patterns of Faces in Young Children - Christou, Antonios I.; Wallis, Yvonne; Bair, Hayley; Crawford, Hayley; Frisson, Steven; Zeegers, Maurice P.; McCleery, Joseph P. (Frontiers in Behavioral Neuroscience, 2015)
Previous studies have documented both neuroplasticity-related BDNF Val66Met and emotion regulation-related 5-HTTLPR polymorphisms as genetic variants that contribute to the processing of emotions from faces. More specifically, research has shown the BDNF Met allele and the 5-HTTLPR Short allele to be associated with mechanisms of negative affectivity that relate to susceptibility for psychopathology. We examined visual scanning pathways in response to angry, happy, and neutral faces in relation to BDNF Val66Met and 5-HTTLPR genotyping in 49 children aged 4- to 7-years. Analyses revealed that variations in the visual processing of facial expressions of anger interacted with BDNF Val66Met genotype, such that children who carried at least one low neuroplasticity Met allele exhibited a vigilance-avoidance pattern of visual scanning compared to homozygotes for the high neuroplasticity Val allele. In a separate investigation of eye gaze towards the eye versus mouth regions of neutral faces, we observed that short allele 5-HTTLPR carriers exhibited reduced looking at the eye region compared with those with the higher serotonin uptake Long allele. Together, these findings suggest that genetic mechanisms early in life may influence the establishment of patterns of visual scanning of environmental stressors, which in conjunction with other factors such as negative life events may lead to psychological difficulties and disorders in the later adolescent and adult years.